Effect of Three Pickling Agents on the Physico-chemical Properties of Two Varieties of Cucumber Stored under Tropical Ambient Conditions - , A. Boakye- Dankwa; , B. K. Maleekuu; , P. Kumah; , P. K. Tandoh (Archives of Current Research International, 2020)
The experiment was conducted to determine the effect of three pickling agents on the physico-chemical properties of two varieties of cucumber (Poinsett and Marketmore) stored under ambient conditions for 90 days. A 2x3 factorial design in a Completely Randomized Design with 3 replications was used for the study. The treatment consisted of two varieties of cucumbers (Poinsett and Marketmore) and three pickling solutions (Brine, Vinegar and Brine + Vinegar). The study revealed that Brine + Vinegar solution recorded the highest firmness (19.17N) whiles Brine solution recorded the least firmness of 8.25N. For the pH, there were no significant differences between the two varieties of cucumber, the pickling solutions and their interaction. Brine + Vinegar solution recorded the highest titratable acidity (12.03%) whiles Brine solution recorded the least titratable acidity (3.90%). For the interaction, Marketmore in Brine + Vinegar recorded the highest mean (13.10%), whiles Marketmore and Poinsett in Brine recorded the least means for titratable acidity (3.73% and 4.07% respectively). For the total soluble solids, no significant difference was observed between the two varieties. Brine solution and Brine + Vinegar solution recorded the highest total soluble solids (3.70 Brix and 3.01 Brix respectively). Vinegar solution recorded the least (1.65 Brix) total soluble solids. For the interaction, Marketmore and Poinsett in Brine recorded the highest total soluble solid (3.67 Brix and 3.73 Brix respectively) while Marketmore and Poinsett in Vinegar recorded the least mean for the total soluble solid content (1.63 Brix and 1.67 Brix respectively).